Layanan Bimbingan dan Konseling untuk Meningkatkan Spiritualitas Keluarga melalui Pesan-Pesan Sejarah dalam Al-Qur'an dan Hadits - Amirullah, Muhammad; Fitriana, Fitriana; Azwar, Azwar (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2025)
The family, especially parents, has the significant influence to the development of the individual's life. This study was conducted with the aim to discuss the nature of the family and its important role in building child spirituality as well as the implementation of Sirah as a medium in building the child spirituality. This research is qualitative descriptive research through library research and content analysis method. The results showed that the family plays an important role in the development of individuals and in various dimensions of their development. Therefore, family (especially parents) need to play an active role in building a variety of positive values in individuals from a young age as provisions in facing life. Spirituality is one of the most important provisions to be developed in individuals because it can have a positive influence on various aspects such as, mental health (depression, anxiety, post traumatic syndrome, schizophrenia), personal skills (copying stress, self esteem, social behavior, commitment to work), and preventing drug abuse and suicidal impulses. Storytelling can be a means to cultivate various positive characteristics in individuals, one of which is spirituality. Islam as a religion rich in educational treasures is very concerned about history. Even the Holy Book of Muslims (Qur'an) contains many stories about history, as well as the hadiths of the Prophet. The goal is for people to learn lessons and lessons. So it can be said that storytelling based on Islamic history (Sirah) can be done as a medium to increase spirituality in the family.